Pengaruh Kinerja Keuangan terhadap Harga Saham Perusahan Properti dan Real Estate Yang Terdaftar di Bursa Efek Indonesia - Uswatun Hasanah; Sutia Budi (Indonesian Journal of Economics Application (IJEA), 2021)
In investing in stocks, investors will choose companies with good financial performance. Investors need information regarding stock developments and financial reports in stock analysis for decision-making. This study analyzes the effect of financial performance on the stock prices of property and real estate companies listed on the Indonesian stock exchange in 2014-2018. The research sample consisted of 15 companies using the purposive sampling technique. The analysis technique used is multiple linear regression with statistical tools SSS version 19. Based on the data analysis results, partially, the debt to equity ratio has a significant effect on stock prices with a significance value of 0.001 <0.05. Return on equity has a significant impact on stock prices with a significance value of 0.014 <0.05. Earning per share has a substantial effect on stock prices with a significance value of 0.000 <0.05. Meanwhile, simultaneously, it shows that the debt to equity ratio, return on equity, and earnings per share significantly affect stock prices with a significance value of 0.000 <0.05.